Deceptive Ceropegia dolichophylla fools its kleptoparasitic fly pollinators with exceptional floral scent - Heiduk, Annemarie; Kong, Hanghui; Brake, Irina; von Tschirnhaus, Michael; Tolasch, Till; Tröger, Armin; Wittenberg, Elisabeth; Francke, Wittko; Meve, Ulrich; Dötterl, Stefan (Frontiers in Ecology and Evolution, 2015)
Ceropegia species (Apocynaceae) have deceptive pitfall flowers and exploit small flies as pollinators, supposedly by chemical mimicry. Only preliminary data on the composition of flower scents are available for a single species so far, and the mimicry system is not yet understood in any species. We collected data on basic pollination aspects of C. dolichophylla, analyzed floral scent by gas chromatography linked to mass spectrometry, identified electrophysiologically active scent components by gas chromatography coupled with electroantennographic detection, and determined compounds responsible for pollinator attraction in bioassays. We found that flowers of C. dolichophylla are visited by small flies of several taxa. Only Milichiidae and Chloropidae carried pollinaria and are, thus, pollinators. The pollen transfer efficiency at two different sites was 2 % and 4 %, respectively. The floral scent was dominated by spiroacetals, mainly (2S,6R,8S)-8-methyl-2-propyl-1,7-dioxaspiro[5.5]undecane, n-tridecane, and N-(3-methylbutyl)acetamide. This spiroacetal and the acetamide elicited the most intense electrophysiological responses in fly antennae, and bioassays confirmed the capability of the spiroacetal in eliciting behavioral responses in pollinators. Most flies, determined as pollinators of C. dolichophylla, are kleptoparasites. They exploit insect prey of predatory arthropods as food source to which they are attracted by volatiles. 8-Methyl-2-propyl-1,7-dioxaspiro[5.5]undecane and N-(3-methylbutyl)acetamide have not been identified before as volatiles of other plants, however, they are known as insect volatiles. Both compounds occur in the venom glands of paper wasps, a potential food source for the pollinators of C. dolichophylla. We propose that C. dolichophylla shows a kleptomyiophilous pollination strategy. It mimics insect related odors to exploit the food-seeking behavior of its kleptoparasitic pollinators.